آليات رقابة الدولة على التجارة الخارجية و حركة رؤوس الأموال - إدريس, سالمي; علي, مصطفاوي; عبد القادر, ملوكة; أحمد, جخراب (University of eloued جامعة الوادي, 2020)
"هدفت الدراسة إلى تسليط الضوء على موضوع آليات الرقابة على التجارة الخارجية و حركة رؤوس الأموال دراسة حالة الجزائر، وذلك من خلال الإشكالية الرئيسية التالية ما مدى نجاعة آليات رقابة الدولة على التجارة الخارجية و حركة رؤوس الأموال في الجزائر؟ إذ تعد رؤوس الأموال الشريان الذي يغذي الاقتصاد و يساهم في الحركية الاقتصادية الوطنية و كذلك تحرير التجارة الخارجية و الوصول إلى الهدف المنشود و هو تنويع الصادرات و التخلص من قيود المحروقات. و قد هدفت أيضا إلى توضيح فعالية الأنظمة الرقابية كآلية للحد من ظاهرة الفساد المالي والإداري و التلاعبات المالية وهي من الظواهر الخطيرة التي تواجه الاقتصاد الوطني ككل وعلى المؤسسات الجزائرية خصوصا . وخلصت الدراسة إلى وجود دور فعال وكبير للنظام الرقابي في كشف فشل الأساليب التقليدية في منع مسببات تلك الانهيارات والفضائح، والتي كان لظهورها آثار مدوية ونتائج مدمرة على الاقتصاد الجزائري الأمر الذي دفع الجهات المعنية إلى إجراء دراسات معمقة لتقييم نظام الرقابة و تحديد الأسباب الرئيسية التي كانت وراء حدوث الأزمات والانهيارات ، وتوفير قدر كبير من الشفافية والإفصاح. ""The study aimed to shed light on the issue of the mechanisms of control over foreign trade and capital movement, a case study of Algeria, through the following main problematic: What is the extent of the contribution of state control mechanisms in reconciling foreign trade and capital movement? As capital is the artery that nourishes the economy and contributes to the national economic movement, as well as the liberalization of foreign trade and reaching the desired goal, which is to diversify exports and get rid of fuel restrictions. This study also aimed to clarify the effectiveness of control systems as a mechanism to reduce the phenomenon of financial and administrative corruption and financial manipulations, which is one of the dangerous phenomena facing the national economy as a whole and on Algerian institutions in particular. The study concluded that there is an effective and big role for the monitoring system in revealing the failure of the traditional methods to prevent the causes of these collapses and scandals, which have had disastrous effects on the Algerian economy. This led the concerned parties to conduct in-depth studies to evaluate the control system and identify the main causes of crises and collapses, and to provide a great deal of transparency and disclosure."
مذكرة مالية و تجارة دولية
Keywords: التجارة الخارجية ، آليات الرقابة، حركة رؤوس الأموال; Foreign trade, control mechanisms, capital movement